1949
DOI: 10.1103/physrev.75.270
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Absorption Spectrum of OCS

Abstract: Extended measurements in the microwave rotational spectrum of carbonylsulfide (OCS) are presented and correlated with the data obtained by other investigators. Precision measurements of rotational transitions for Jl-J2-; J J4-5 allow the evaluation of precise reciprocal moments of inertia in the ground vibrational state, and the centrifugal distortion coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1949
1949
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…It was observed that the splitting between the e and f sub-states increases with increasing J value and subsequently the l-type doubling constant was calculated. The variation of J 2 n D ( ) / with (J+1) is shown in figure 3 and the slope of the straight line provides the l-type doubling constant [22,23]. In our present study, the l-type doubling constant for (14 2 0) vibrational state was found to be (2.41±0.3)×10 −5 cm −1 which is ∼10 times smaller than the value of the l-type doubling constant for l=1 state of OCS.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the splitting between the e and f sub-states increases with increasing J value and subsequently the l-type doubling constant was calculated. The variation of J 2 n D ( ) / with (J+1) is shown in figure 3 and the slope of the straight line provides the l-type doubling constant [22,23]. In our present study, the l-type doubling constant for (14 2 0) vibrational state was found to be (2.41±0.3)×10 −5 cm −1 which is ∼10 times smaller than the value of the l-type doubling constant for l=1 state of OCS.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental work was carried out with a standard Stark-modulated spectrograph that has been described elsewhere (6). A K-band klystron output was frequency doubled with a crystal doubler to the required range because of the lack of a frequency source in the region of this transition (48,000 Me/sec).…”
Section: Methyl Alcoholmentioning
confidence: 99%
“…In Ref. 1 we have shown that a ratio of vibrational moments of inertia is exact to zero order, and experience with OCS has shown that in fact such a ratio is good to better than .1 per cent. For the present we car say no more until the change of M 3 with selenium mass is determined.…”
Section: Se80mentioning
confidence: 99%
“…5 The sweep spectroscope and frequency standard described in Ref. 1 were used in measuring the absorption frequencies. The signal generators for the J = 2-*3 were reflex klystrons; for the J = 5-6 and the J = 6-*7 absorption transitions were measured with the second harmonic porer generated in silicon crystals driven by standard klystrons.…”
Section: Eerimentalmentioning
confidence: 99%
See 1 more Smart Citation